2018
DOI: 10.3390/ijerph15081597
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Heat-Related Mortality Risks among Rural Populations: A Systematic Review and Meta-Analysis of Epidemiological Evidence

Abstract: Most epidemiological studies of high temperature effects on mortality have focused on urban settings, while heat-related health risks in rural areas remain underexplored. To date there has been no meta-analysis of epidemiologic literature concerning heat-related mortality in rural settings. This study aims to systematically review the current literature for assessing heat-related mortality risk among rural populations. We conducted a comprehensive literature search using PubMed, Web of Science, and Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…24-26 30 33 34 55 58 60 62 77-89 A strong association was reported between heat (including heat waves) and mortality (all-cause), 77 heat related, 55 81 stroke related, 24 82 cardiovascular related, 33 60 and respiratory related, 26 33 83 especially in rural, 80 very young children 62 and ageing populations. 25 Mortality seems to be the most frequent health outcome studied in association with heatwaves. 34 Inconsistent results are found concerning the association between heat and childhood mortality.…”
Section: Meteorological 24mentioning
confidence: 99%
“…24-26 30 33 34 55 58 60 62 77-89 A strong association was reported between heat (including heat waves) and mortality (all-cause), 77 heat related, 55 81 stroke related, 24 82 cardiovascular related, 33 60 and respiratory related, 26 33 83 especially in rural, 80 very young children 62 and ageing populations. 25 Mortality seems to be the most frequent health outcome studied in association with heatwaves. 34 Inconsistent results are found concerning the association between heat and childhood mortality.…”
Section: Meteorological 24mentioning
confidence: 99%
“…Studies of the effects of heat and cold on mortality have increased in the last two decades, due in large part to researchers' attempts to measure the impact of global climate change, which is characterized by an increase in global average surface temperature as well as an increase in the number, duration, and frequency of extreme weather events. 1 As a result, many literature reviews have examined the evidence for associations of mortality with both heat and cold, [2][3][4][5][6][7][8][9][10][11][12][13][14] with recent reviews also focusing on temperature variability, coverage. The search for exposure centered on temperature: "temperature" OR "extreme weather" OR "extreme weather events" OR "climate change" OR "extreme temperature" OR "cold" OR "heat" OR "cold temperature" OR "hot temperature" OR "cold spell" OR "heat wave."…”
Section: Introductionmentioning
confidence: 99%
“…Most reviews concluded by calling for more research, noting the limitations observed among the studies included in their reviews, as well as limitations in their reviews themselves. These limitations included, amongst others, some systematic reviews having a small number of publications, 27,28 language restrictions such as including only papers in English, 20,23 arriving at conflicting evidence, 29 difficulty concluding a strong association due to the heterogeneity in methods and measurements or the limited equipment and access to quality data in certain contexts, 27,30–32 and most studies included were conducted in high-income countries. 33,34…”
Section: Resultsmentioning
confidence: 99%